Structures of the intermediates of Kok’s photosynthetic water oxidation clock - Kern, Jan F.; Chatterjee, Ruchira; Young, Iris D.; Fuller, Franklin D.; Lassalle, Louise; Ibrahim, Mohamed; Gul, Sheraz; Fransson, Thomas; Brewster, Aaron S.; Alonso-Mori, Roberto; Hussein, Rana; Zhang, Miao; et al. (Nature, 2018)
Crystallography and spectroscopy are used to solve high-resolution structures of the intermediates of Kok’s S-state clock in photosystem II.
Gesehen am 24.10.2019